Introduction to Marine Genomics - Cock, J. Mark; Tessmar-Raible, Kristin; Boyen, Catherine; Viard, Frédérique (Advances in Marine Genomics, 2010)
Marine biology has always played an important role in biological research, being at the origin of many key advances. To a certain extent, the influence of marine biology on the biological sciences was overshadowed over a period of several years by the remarkable advances that were made using powerful model organisms from terrestrial environments. This situation is now changing again, however, due primarily to spectacular developments in genomic methodologies that have significantly accelerated research in a broad spectrum of marine biology disciplines ranging from biodiversity to developmental biology to biotechnology. The data generated by marine genomics projects have had an impact on questions as diverse as understanding planetary geochemical cycles, the impact of climate change on marine fauna and flora, the functioning of marine ecosystems, the discovery of new organisms and novel biomolecules, and investigation of the evolution of animal developmental complexity. This book represents the first attempt to document how genomic technologies are revolutionising these diverse domains of marine biology. Each chapter of this book looks at how these technologies are being employed in a specific domain of marine research and provides a summary of the major results obtained to date. The book as a whole provides an overview of marine genomics as a discipline and represents an ideal starting point for exploring this rapidly developing domain.